Customer-Committed How to Create Outstanding Customer Experiences and Strengthen Your Brand - Weber, Mathias (Springer Fachmedien Wiesbaden : Imprint: Springer, 2025)
XIII, 140 p. 52 illus., 1 illus. in color.